USING DEXMEDETOMIDINE AS THE MAIN AGENT FOR ANESTHETIC MANAGEMENT DURING RADIOSURGERY IN A CHILD - A. M. Аrefiev; A. Yu. Lubnin; A. S. Kulikov (Вестник анестезиологии и реаниматологии)
This clinical case demonstrates specific features of anesthetic management during radiosurgery in pediatric patients considering the limited access to them during continuous manipulations with pharmacological sedation. Considering the age of the child, dexmedetomidine, the drug from the group of agonists of α2-adrenergic receptors, was used as the main agent. It was used since it could be administred by the noninvasive way for premedication and intravenously in a form of infusion to provide the necessary depth of sedation with preservation of spontaneous breathing and minimization of uncontrolled motions of the patient.